Case Report: Human Recombinant Growth Hormone Therapy in a DSH Cat Presented With Dwarfism - Načeradská, Martina; Návojová Horáčková, Kateřina; Fridrichová, Michaela (Frontiers in Veterinary Science, 2021)
A 6-month-old kitten, male, domestic shorthair cat was presented with dwarfism, ocular and nasal discharge, and Ascaris infestation. Congenital hyposomatotropism was diagnosed on the basis of serum level of insulin-like growth factor-1 (IGF-I). The cat was treated with human recombinant growth hormone for 9 weeks. After that, his liver enzymes became elevated, and the therapy was discontinued. His IGF-I levels were normal at the end of the therapy. Normal IGF-I was present 3 months after discontinuation of therapy with human recombinant growth hormone and even half a year after the discontinuation. All other comorbidities were addressed with the therapy. The cat is now the size of normal cats, living with the first author.